2021
DOI: 10.1016/j.nutos.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Olive leaf powder prevents nonalcoholic steatohepatitis in Sprague–Dawley rats fed a high-fat and high-cholesterol diet

Abstract: Conclusions: Our results suggest that OLP possesses a preventive effect against NASH progression, presumably due to the elevated serum adiponectin levels and its anti-oxidative properties. Because this preventive effect was not dose-dependent, further studies are needed to investigate the optimal dose of OLP for obtaining the maximum preventive effects against NASH, and to elucidate the detailed pharmacological mechanism(s) of OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Wren-Dail et al reported that blood glucose concentrations in the SD rats received anesthesia with isoflurane were significantly higher (1836 3 mg/dL) than those received brief CO2 anesthesia (1326 2 mg/dL) (15). Indeed, the blood glucose level after 8 h of fasting in the SD rats received anesthesia with isoflurane and pentobarbital at 18 wk of age was 186.16 9.0 mg/dL in our previous study (16). Therefore, the N group can be considered as con-trol group in the present study, but the better method of anesthesia or euthanasia by decapitation which does not affect the blood glucose metabolism should be used in the future study.…”
Section: Discussionmentioning
confidence: 88%
“…Wren-Dail et al reported that blood glucose concentrations in the SD rats received anesthesia with isoflurane were significantly higher (1836 3 mg/dL) than those received brief CO2 anesthesia (1326 2 mg/dL) (15). Indeed, the blood glucose level after 8 h of fasting in the SD rats received anesthesia with isoflurane and pentobarbital at 18 wk of age was 186.16 9.0 mg/dL in our previous study (16). Therefore, the N group can be considered as con-trol group in the present study, but the better method of anesthesia or euthanasia by decapitation which does not affect the blood glucose metabolism should be used in the future study.…”
Section: Discussionmentioning
confidence: 88%
“…If the glycosidic bond is broken, glucose is released, and oleuropein aglycone, with the help of water, is quickly converted into the dialdehyde form of decarboxymethyl oleanolate acid (21). Numerous crucial parameters, such as pH, the type of organic acid and time, as well as combinations of these factors, related to the quantity of purification of hydroxytyrosol isolates, affect the hydrolysis of oleuropein to hydroxytyrosol (22). Various methods for the isolation of oleuropein (Table 1) and hydroxytyrosol (Table 2) have been developed, including standard and modified versions.…”
Section: Characteristics and Extraction Methods Of Oleuropein And Hyd...mentioning
confidence: 99%